KOMUNIKASI PUSTAKAWAN - khatibah khatibah (UIN Sumatera Utara, 2014)
Communication is the role of communication sciences to the library, any institutions has a close relationship with communication including the library.An institution is difficult to develop and progress without communication,especially librarians who have a duty as an exellent service to users. If the library has the expertise and proficient in communicating, then there will be positive image to users, so users have a positive attitude to the library